Role of Smart Contracts in Halal Supply Chain Management - Fernando, Yudi; Mohd Ridzuan, Darun; Al-haimi, Basheer; Daing Nasir, Ibrahim; Tieman, Marco; Fazeeda, Mohamad (IGI Global, 2021)
Now, more than ever, with the existence of the new blockchain technology, smart contracts started its revolution. Although the industry has been practices smart contracts using blockchain technology, limited study available on how blockchain technology contributes to Halal supply chain management. Thus, the aim of this chapter is to review the roles, promises and benefits of smart contracts based on blockchain technology for Halal supply chain management applications. An extensive literature exploration is conducted to reveal the existing literature on smart contracts using blockchain technology. The authors have faith in that the findings in this chapter can be used as a solid base for the researchers and practitioners of smart contracts in Halal supply chain management